PELAKSANAAN FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN DESA TERHADAP PENGELOLAAN DANA DESA TAHUN ANGGARAN 2020 DI DESA WEULUN KECAMATAN WEWIKU KABUPATEN MALAKA - Bria, Frederikus Dion; Monteiro, Yosef M; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
The problem that occurred in Weulun Village was that the Weulun Village Head was not transparent regarding the management of village funds so that the Weulun Village Head was reported by the residents to the Malaka Regency DPRD office. This can be proven by one of the residents of D Weulun who stated that the Village Head was considered not transparent and everything was done internally without involving community members so that Weulun Village resident reported it to the Malaka Regency DPRD office. As for BPD supervision of the village heads performance in managing Yanuarius Tae Seran village in the 2020 Fiscal Year. This research is empirical research, namely research carried out in connection with direct data collection in the field. This research was conducted in weulun Village and the Malaka Regency DPRD Oficce. Data processing was carried out using data obtained from both primary data and secondary data and analyzed descriptively-qualit atively.The results of this research show that (1) the performance of the village head in managing village funds is not in accordance with the applicable law, namely it is not transparent, open and accountable, the BPD in monitoring the performance of the village head regarding village funds is optimal, the supervision carried out is in accordance wit the law. Applicable law. In this research, the author suggests that the selection of village heads must be in accordance with the criteria, knowledge, education (2) factors that hinder the BPD in supervising the management of village funds related to the performance of village heads including human resources, infranstructure and communication. In this research the author suggests that the selection of village heads must be in accordance with criteria, knowledge and education.